FREQUENCY OF COMPLICATIONS IN WOMEN AFTER INDUCED ABORTION PRESENTING AT THE OBSTETRICAL EMERGENCY OF SAHIWAL TEACHING HOSPITAL, SAHIWAL (The Research of Medical Science Review, 2024)
To assess the frequency and types of complications in women presenting at obstetrical emergency departments after an induced abortion, This descriptive, cross-sectional study was conducted at the Department of Obstetrics & Gynecology at Sahiwal Teaching Hospital, Sahiwal. The WHO sample size calculator determined a sample size of 159 cases, with a 95% confidence level, a 4% margin of error, and an expected percentage of pelvic peritonitis of 7.1%. Data were collected through non-probability, and consecutive sampling was used to select participants, The mean age of participants was 27.4 years (±5.8), and the median gestational age was 10 weeks. The most common complications were genital hemorrhage (35%), anemia (30%), and septic abortion (20%). Women with gestational ages >12 weeks and those from rural areas showed significantly higher complication rates, It is concluded that women presenting after induced abortion frequently experience severe complications, with higher rates observed in rural residents and those with advanced gestational age. This calls for improved access to safe abortion and post-abortion care, particularly in underserved populations.